Study of implicit information semi-supervised learning algorithm - Guo-dong LIU; Jing XU; Guo-bing ZHANG (Tongxin xuebao)
Implicit information semi supervised learning algorithm was studied.The implicit information semi supervised learning algorithm was used in support vector machine and random forest,which were called semi-SVM and semi-RF.The semi-SVM and semi-RF were evaluated by using UCI,the experimental results show that the semi-SVM and semi-RF are more effective and more precise.The semi-SVM and semi-RF were applied to classifying lung sounds,and verified the effect by using the actual lung sounds data.the quantity and quality of samples affect semi-SVM and semi-RF were analyzed.